The effectiveness of ODL method for ENT530 during the pandemic of COVID-19 / Law Kuan Kheng ...[et al.] - Law, Kuan Kheng; Suffarruddin, Suhaida Herni; Khamis, Muhammad Sazri (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The pandemic of Covid-19 and execution of lockdowns like Movement Control Order (MCO) since March 18, 2020 in Malaysia have impacted many people, industries and institutions. There are many things or new norms needs to be adapted by Malaysians such as practising social distancing, wearing face mask, hand sanitizing, cleaning surfaces regularly and avoiding crowed places. Besides, this coronavirus outbreak has also affected the operation of education systems in Malaysia and the government had to take drastic action by closing schools and universities that involved millions of pupils and students. Approximately 1.2 million students in higher education institutions (HEIs) (across public and private universities, polytechnics, and community colleges), including all campuses of Universiti Teknologi MARA (UiTM) across Malaysia were affected by this closure (Daniel Rahman, 2020, March 24).